Pengaruh Metode Muhadharah Terhadap Kemampuan Bahasa Arab Santri Di Pondok Pesantren Darularafah Raya - Farida Khairani Siregar; Hasrian Rudi Setiawan (Al-Ulum: Jurnal Pendidikan Islam, 2023)
The main problem in this study is the lack of students’ Arabic language skills. The incubation of the muhadharah method aims to find out how the effect of the muhadharah method has on the Arabic language skills of students at Darularafah Raya Islamic Boarding School. This study uses a type of correlational quantitative research. The subjects in this study were school principals, educators and students at the darularafah raya Islamic boarding school. The population used was 450 students and the sample used was 100 students by using the slovin formula. Data collection techniques are in the form of questionnaires, tests and documentation. The independent variable in the study was the muhadharah method while the dependent variable was the students’ Arabic language ability. As for the results of the t-test in this study, it shows that the calculated t-value is 20,768 with a significance level of 5%, which is greater than the t-rabel of 1,987 with a significance value of 0,000 < 0,05, so it can be said that the muhadharah method affects the students’ Arabic language skills so that prove that ha is accepted. As well as the results of the F test (Simultaneous Test) shows that Ha is accepted and Ho is rejected, which means that the muhadharah method affects Arabic language skills.